107k views
1 vote
Simplify the following expressions.

1. 3( x - 5 ) + 2x - 3

2. 4a - 3 ( 4 - a )

3. -2 ( b - 6 ) + 2

4. 6 - 3 ( 3 + x )

1 Answer

4 votes

Explanation:

1. 3( x - 5 ) + 2x - 3

= 3x - 15 + 2x - 3

= 5x - 18

2. 4a - 3 ( 4 - a )

= 4a - 12 + a

= 5a - 12

3. -2 ( b - 6 ) + 2

= -2b + 12 + 2

= -2b + 14

= 14 - 2b

4. 6 - 3 ( 3 + x )

= 6 - 9 - 3x

= -3 - 3x

User Shujaath Khan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.